Xenotime reveals Caledonian hydrothermal overprint on Neoproterozoic Cu mineralization, East Greenland - Olierook, Hugo K. H.; Crook, K.; Sinclair, P.; Fougerouse, Denis; Joseph, C.; Kirkland, Christopher L.; Kennedy, Allen; Gao, Hao; Evans, Noreen; McDonald, Bradley J.; Quintero, Raiza R.; Kumara, Anusha Shantha; et al. (2023)
Constraining the age of many types of ore deposits remains challenging because of the lack of radiogenic isotopes incorporated into common ore-forming minerals. The timing of pre-Caledonian-hosted Cu mineralization along the entire c. 1200 km long East Greenland Caledonides remains virtually unknown, hampering our knowledge of ore deposit timing and genesis in a frontier exploration region. Here, automated mineral analysis of a series of nodular, disseminated and vein-hosted Cu-± Pb-mineralized metasedimentary rocks in central East Greenland reveals detrital zircon and hydrothermal xenotime, both amenable to U–Pb geochronology. Detrital zircon geochronology of a co-deposited quartzite reveals an age distribution highly similar to the Cryogenian (c. 700 Ma) upper Eleanore Bay Supergroup. Hydrothermal xenotime U–Pb analyses adjacent to nodular and disseminated chalcocite across three proximal samples have variable amounts of common Pb that together yield a well-defined single discordia with a lower concordia intercept of 438 ± 13 Ma (2σ). This age is within uncertainty of the onset of Caledonian regional metamorphism and granitoid production and clearly post-dates deposition of the upper Eleanore Bay Supergroup by several hundred million years. Considering a published chalcocite Pb–Pb isochron age of 680 ± 65 Ma, the hydrothermal xenotime U–Pb ages imply that Caledonian-driven fluid activity, sourced from metamorphic reactions or from granitoids, remobilized diagenetic Cu and Pb mineralization. Chalcocite Pb–Pb isotopes show that dissolved and reprecipitated portions are volumetrically minor, radiogenic and Pb-poor, implying that fluids stripped most of the Pb from the system. Thus, it is likely that remobilization was localized on the grain scale, although some Cu and Pb was transported away from diagenetic sites, perhaps into veins. Although Caledonian metamorphism and granitoid emplacement is widespread in central East Greenland, the full extent of their roles in upgrading Cu mineralization remains to be ascertained.